Evaluating User Experience of a Mobile Health Application ‘Halodoc’ using User Experience Questionnaire and Usability Testing - Mochammad Aldi Kushendriawan; Harry Budi Santoso; Panca O. Hadi Putra; Martin Schrepp (Faculty of Computer Science Universitas Indonesia, 2021)
This paper aims to evaluate the user experience of a mobile health application called Halodoc to keep the user using the application and keep from losing a potential source of revenue for Halodoc. Halodoc is one of the companies that use the internet to provide health services for its users. Halodoc has services such as features for consultation with doctors, online medicine purchases, and hospital appointments. Halodoc’s vision is to simplifying healthcare, but there are still many complaints and negative reviews about Halodoc on Google play store and Apple store about the usability. This paper uses a mixed-method approach using User Experience Questionnaire (UEQ) and Usability Testing. The results of the analysis were used as a reference for making the improvement designs. The results of the UEQ evaluation showed accordingly to the UEQ benchmark already a good level of UX. However, the usability test uncovered some concrete areas for improvement.